Why and how should design patterns be formalized? - Taibi, T; Ngo, DCL (2001)
Textual descriptions of design patterns are ambiguous and may lead to conflicting interpretations. Since patterns are meant for communication and education, a correct and complete understanding is a prerequisite to their successful usage. Formal specification of design patterns is meant to complement existing textual descriptions. Formal specification allows a rigorous reasoning of design patterns and facilitates tool support for their usage.